Effectiveness of Small Group Discussion Sessions in Teaching Biochemistry for Undergraduate Medical Students - Muhammad Muizz Hassan, Maryam Mastoor, Imran Khawaja, Saman Fatima, Muhammad Abdullah Avais, Gul Muhammad Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Background and aim: Teaching is an important part of the medical curriculum. Different teaching methods include small group discussions, demonstrations, inquiry approaches, lectures, problem solving methods, and tutorials. Group discussions are at the core of medical education because they help students learn more effectively. As a result, the current study sought to analyze the efficacy of small group discussions in teaching biochemistry to undergraduate medical students. Place and Duration: Gomal Medical College MTI, Dera Ismail Khan and Department of Biochemistry of Amna Inayat Medical College Lahore for the duration from March 2022 to August 2022. Method: This study included 50 undergraduate medical students of first year registered in international medical program. Prior to study conduction, ethical approval and informed written consent was taken. Student’s perception regarding small group discussion sessions were elicited based on unknown questionnaires provided to them. Likert scale was used to show their level of agreement with the questionnaire’s claims. Results: Of the 50 undergraduate medical students, 28 (56%) were male and 22 (44%) were females students. About 64.6% (n=32) students believed that their grasp over the study material improved with small group discussion and 52.4% (n=26) agreed to the facilitation of active learning in small group discussion. Communication skills and clinical reasoning improved by small group discussion were claimed by 36% (n=18) medical students. Majority of undergraduate medical students 68% (n=34) strongly agreed to the claims that small group discussion helped them to correlate medical problems with biochemical concepts. Conclusion: The present study concluded that small group discussion in combination with lectures appears to provide the best instruction for the learner or medical students. Mostly students emphasized on importance of small group discussion in terms of topic better comprehension, promoting knowledge, correlation of biochemical ideas with medical issues, and interest. Similarly, they discussed the need of developing effective communication skills, as well as leadership and teamwork abilities. Keywords: Medical students, Undergraduate, Small group discussion, Biochemistry, Effectiveness